MANAJEMEN RISIKO PERIKANAN TANGKAP (STUDI KASUS DI TENGAH PANDEMI COVID-19) - Nurhayati, Atikah; Pical, Venda; Erfani, Anthon; Hilyaa, Siti; Saloko, Satrijo; Made, Sutinah; Purnomo, Agus Heri (JFMR (Journal of Fisheries and Marine Research), 2020)
The spread of the Coronavirus outbreak has had an impact on the fisheries sector. The spread of the Corona Virus has brought new challenges and risks in social life, including capture fisheries products. Disruption of supply chain between business actors and consumers due to restrictions on human mobility that were implemented to overcome the Covid-19 outbreak. This reserach aims to analyze the fisheries risk management case study in pandemic Covid-19. This research was conducted in April - September 2020. The data used are primary and secondary data. Primary data obtained by taking non-probability sampling techniques to 50 respondents of capture fisheries business actors, using health protocols. Secondary data were obtained using literature studies. The analytical tool used in this research is descriptive analysis. Based on the results of research, the risks received by capture fisheries business actors include the risk of the capture fisheries production process during the Covid-19 pandemic, the risk of collaborating with capture fisheries production during the Covid-19 pandemic, the risk of decision making during the Covid-19 pandemic, the risk of product market capture fisheries during a pandemic. Adaptation strategies should be done undertaken by fishery business actors by optimizing the function and role of fishery cooperatives, strengthening marine and fisheries financial institutions, strategies for adapting fisheries marketing through a warehouse receipt system.